Place and role of science-intensive business segments in vertically integrated oil and gas companies - K. G. Kachalkina (Вестник университета)
Oil and gas industry development is influenced by global trends, which are mostly negative and restrictive in nature. Improvement and applied use of scientific resources are some of the key factors that allow us to respond to the challenges. The relevance of knowledge-intensive business segment development is noted by the industry expert community. The current versions of the Energy Strategy and the Strategy for Scientific and Technical Development of Fuel and Energy Sector Industries include tasks of developing import-substituting technologies and equipment, conducting R&D for this purpose, and improving scientific competencies. These tasks are translated into the strategies of individual vertically integrated oil and gas companies, and, therefore, there is a need to analyze the place and role of knowledge-intensive business segment of such companies in order to assess its ability to ensure their strategic sustainable development. According to the analysis results, importance of knowledge-intensive business segment for strategic sustainable development of oil and gas companies has been confirmed. The need to actualize the tools and methods of strategic planning for knowledge-intensive segments development in order to align activity to create scientific results with formalized goals and challenges of company development has been identified.